(untitled) (Journal of Fatima Jinnah Medical University, 2022)
Background: The current study aimed to determine the effect of video games among the Non-Video-Game Addicted (NVGA) and Video Game Addicted (VGA) in terms of mental health and physical activity among adolescents from Karachi. Subjects and methods: A cross-sectional study was conducted at public sector schools and colleges of different socioeconomic status of Karachi, Pakistan, from Jan-March 2020. Total of 321 students, adolescents, aged from 15-19 years, from both genders and who used to play video games but were considered as non-video game adictors (using less than four hours per day on video games) and video game adictors (using more than 5 hours per day). Questionnaires were used to collect data based on DSM-5 to find gaming addiction in adolescents with 21 questions. "General Health Questionnaire (GHQ)," with 14 questions on mental health. "International Physical Activity Questionnaire," for physical activity status. Students were divided into two groups: non-video game addicted (NVGA) and video game addicted (VGA). Results: Out of 321, 233 (72.6%) were VGA, and 88 (27.4%) were NVGA students. There were 184 (57.3%) males and 137 (42.7%) females. The mean addiction score was 2.221+0.49 and 3.34+0.35 in the VGA group and NVGA group, respectively. 19.0% of males and 8.4% of females were VGA. Variables used for video game addiction in the study were salience, tolerance to play the game, mood modification, relapse, withdrawal, conflict, and problems (such as sleep deprivation, etc.). The mean score for all these variables was higher in the VGA group (p<0.001). The mean score of MHQ responses was significantly higher in the VGA group, indicating the high intensity of distress. Conclusion: It has been concluded from the study that a very high frequency of video game addiction in adolescents (VGA group) caused mental and physical health problems in the study population.